Pitched! Informants and the covert policing of football fans in Scotland. (9th August 2021) - Atkinson, Colin; McBride, Maureen; Moore, Allan
ABSTRACT: This paper offers a new perspective on the policing of football fans by exploring the recruitment and use of 'informants', or 'Covert Human Intelligence Sources' (CHIS), in this area of police practice. Drawing upon semi-structured interviews with both football fans and police officers in Scotland we foreground fan experiences against a backdrop where intensive police surveillance has become a routine feature of football events. In particular, our research uniquely provides accounts of fans whom the police sought to recruit as informants, a process known colloquially in policing as being 'pitched'. In doing so we highlight the impact this tactic has on football fans, both individually and collectively. In understanding police perspectives, we note how the use of informants in football policing is frequently justified as a 'legitimate' means to provide intelligence to prevent violence and disorder amongst fans. Cautioning upon the dangers of further 'surveillance creep', we highlight that the use of informants in the policing of football fans and events raises both practical and ethical issues. In particular, we argue that the use of informants in the covert policing of football fans, if this tactic is to be used, must be grounded in a clearly articulated threat of violence and disorder that is accepted by football fans and the wider community. In the absence of this, the use of such tactics is likely to be considered unnecessary and disproportionate by football fans, feeding a wider narrative of criminalisation and a perception of illegitimate and disproportionate forms of policing.